2021
DOI: 10.2174/1573399817666210303095633
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Early Administration of Insulin Glargine in the Acute Management of Diabetic Ketoacidosis

Abstract: Background: Few studies have evaluated the early use of insulin glargine in the management of diabetic ketoacidosis (DKA) patients. Early insulin glargine use in DKA was safe and associated with a trend towards faster DKA resolution. Objectives: To evaluate the efficacy and safety of early insulin glargine administration for acute management of DKA in critically ill patients. Methods: This single-center retrospective cohort study included patients, who were >18 years of age with DKA, admitted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Because of its pharmacokinetic properties, the addition of SC insulin glargine to IV continuous insulin infusion in the early phase of DKA may accelerate DKA resolution by decreasing the requirement for IV insulin infusion and facilitating the transition from continuous IV insulin infusion to SC maintenance therapy. This treatment strategy is supported by several studies that show early glargine administration is effective and appears to be safe 13‐18,22 …”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Because of its pharmacokinetic properties, the addition of SC insulin glargine to IV continuous insulin infusion in the early phase of DKA may accelerate DKA resolution by decreasing the requirement for IV insulin infusion and facilitating the transition from continuous IV insulin infusion to SC maintenance therapy. This treatment strategy is supported by several studies that show early glargine administration is effective and appears to be safe 13‐18,22 …”
Section: Discussionmentioning
confidence: 91%
“…This treatment strategy is supported by several studies that show early glargine administration is effective and appears to be safe. [13][14][15][16][17][18]22 T A B L E 3 Summary of studies associated with the use of early subcutaneous insulin glargine in DKA management Outcomes were from all patients with known diabetes and receiving IV insulin infusion (including with DKA, after solid organ transplantation, and patients with other surgical and medical diagnoses).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of basal insulin while on fixed-rate intravenous insulin infusion is advocated by many clinicians but avoided by others because of the risk of hypoglycaemia [134] or hypokalaemia [135]. Several studies have reported that the coadministration of a low dose (0.15-0.3 U/kg) of basal insulin during insulin infusion reduces time to DKA resolution, duration of insulin infusion [136,137] and length of hospital stay [136] and prevents rebound hyperglycaemia, all without increased risk of hypoglycaemia [136,138,139].…”
Section: Section 4 What Is the Recommended Treatment Of Dka And Hhs?mentioning
confidence: 99%
“…Notably, the current literature demonstrates substantial variability defining DKA resolution, with some trials utilizing an AG ≤ 12 mEq/L, whereas others do not reference transition AG and utilize parameters such as BG, pH, and bicarbonate. [4][5][6] Clinicians may consider transitioning to SQ insulin when AG remains above 12 mEq/L as IV insulin infusions carry risks of hypoglycemia and electrolyte derangements, and may require an ICU level of care. However, no trials to date have analyzed the success rates of insulin transition or patient outcomes when patients are transitioned with an AG ≤ 12 mEq/L versus an AG > 12 mEq/L.…”
Section: Introductionmentioning
confidence: 99%